Drying of fruits and vegetables: The impact of different drying methods on product quality - Hawlader, Mohammad Nurul Alam; Baradey, Y.; Ismail, Ahmad Faris; Hrairi, Meftah (CRC Press, 2016)
Drying is a water removal process from foodstuffs commonly used for preservation and storage purposes. Different drying methods are nowadays available, such as freeze drying, vacuum microwave drying, hot air drying, heat pump drying, and solar-assisted heat pump drying (SAHPD). Fruits and vegetables are very important products for human beings because of their high nutritional values. They are perishable products and contain high percentage of moisture. The moisture content, in some cases, may be more than 90%. Water content is considered the main reason for microorganisms’growth, which leads to putrefaction. Preservation of fruits and vegetables is considered to be a very important step to match availability in agriculture sector and consumers’ utilization to keep it fresh and nutritional as long as possible, and to meet the demand for fast and instant products with high quality. Drying methods are likely to affect the physical, chemical, nutritional, and biological properties of fruits and vegetables. Despite the negative influences that could occur because of moisture removal by drying on the quality of the food, it is still an indispensable process in different sectors of industry, because it provides low packaging costs, increased shelf-life of the foodstuff, and lower shipping weights. In this chapter, the impact of different drying methods on the quality attributes of fruits and vegetables are summarized. From a comparison of all the drying methods available, it is seen that heat pump or SAHPD shows a better retention of nutrients compared to other methods at a reasonably low cost.